Analysis of Blood Cockles Marketing (Anadara granosa) Cultivation Results in Kepenghuluan Panipahan Darat Pasir Limau Kapas Sub District Rokan Hilir Regency Riau Province - Nurlina Nurlina; Eni Yulinda; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in January 2017, located in Kepenghuluan Panipahan Darat Pasir Limau Kapas Subdistrict Rokan Hilir Regency Riau Province.The aims of this research are to find out the pattern of marketing channel of blood cockles (Anadara granosa) in Panipahan Darat, to analyze the cost, profit and margin of the marketing of blood cockles(Anadara granosa) in Panipahan Darat, to know the efficiency level of marketing of blood cockles (Anadara granosa) in Panipahan Darat. The method used in this research is survey method that is by doing direct observation. The number of shellfish cultivators as many as 11 cultivators and farmers' cultivation methods are census. While the sampling of merchants in snowball sampling that consists of 4 merchant collectors, 2 wholesalers and 3 retailers. The results showed that there are three patterns of blood cockles marketing channels in Panipahan Darat Pasir Limau Kapas Sub-district of Rohil Regency. In channel I the total marketing cost is Rp 420 per kg, total marketing profit Rp 3.580 per kg, and marketing margin of Rp 4,000 per kg. While at marketing channel II total marketing cost 760 per kg, total marketing profit Rp 2,240 per kg, and marketing margin Rp 3,000 per kg. For marketing channel III total marketing cost Rp 1,100 per kg, total marketing profit Rp 3,900 per kg, and marketing margin Rp 5,000 per kg. Viewed from the economic marketing efficiency of the three existing marketing channels Kepenghuluan Panipahan Darat Pasir Limau Kapas Sub-district of Rohil Regency, the marketing channel II is the most efficient marketing channel of shellfish with a low marketing margin of 30% and has a high fisherman's share value of 70%. Keywords: Analysis, cost, margin, Profit and marketing efficiency